2017
DOI: 10.1177/0265407517701298
|View full text |Cite
|
Sign up to set email alerts
|

“Don’t bring me down”

Abstract: Ample evidence has shown that secure attachment is related to more positive body-related attitudes in women. However, existing studies are primarily correlational, leaving questions about causal direction unanswered. This article reports results of two experiments that tested the effects of a guided visualization priming procedure on body image. In Experiment 1, 87 female undergraduates completed a neutral prime at Time 1 and were randomly assigned to either a secure or anxious prime at Time 2. They completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2121
2121

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(79 reference statements)
3
2
0
Order By: Relevance
“…The results of indirect coefficients also presented that the indirect effects of attachment styles (avoidance style only) on body image concern, with the mediating role of selfesteem, were significant. This result was in line with those of Salehi et al (2019), Yoon and Kim (2020), Ghanbari Nejad Esfaqan Sari and Zarbakhsh Bahri (2015), Homan et al (2018), Szalai et al (2017), and Davis and Vernon (2002). As a result, attachment is a deep emotional bond, i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of indirect coefficients also presented that the indirect effects of attachment styles (avoidance style only) on body image concern, with the mediating role of selfesteem, were significant. This result was in line with those of Salehi et al (2019), Yoon and Kim (2020), Ghanbari Nejad Esfaqan Sari and Zarbakhsh Bahri (2015), Homan et al (2018), Szalai et al (2017), and Davis and Vernon (2002). As a result, attachment is a deep emotional bond, i.e.…”
Section: Discussionsupporting
confidence: 90%
“…The obtained data demonstrated that only the coefficient of direct avoidance attachment path was significant on body image concern. This result was consistent with those of Salehi et al (2019), Homan et al (2018), Szalai et al (2017, and Davis and Vernon (2002). Khorshidi and Fathi Aqdam (2018) argued that among the types of attachment styles (safe, avoidant, and ambivalent), those with secure attachment styles present a better body image.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results broadly corroborate those previous findings, but also extend them through our utilisation of a more up-to-date measure of body appreciation (i.e., the BAS-2 compared to the BAS), the inclusion of community women and men (as opposed to college women alone), and the use of a sample from a new national context (i.e., Israel). Our findings are consistent with the suggestion that attachment anxiety is associated with poorer body image (Frederick et al, 2015;Homan et al, 2018;Iannantuono & Tylka, 2012;van den Brink et al, 2016), but also that self-compassion mediates the relationship between attachment anxiety and body appreciation (Raque-Bogdan et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…However, of the two constructs, it is attachment anxietybut not attachment avoidance -that has been shown to be significantly associated with less positive body image (Frederick et al, 2015;Iannantuono & Tylka, 2012;van den Brink et al, 2016). In addition, priming anxious attachment has been shown to worsen women's, though not men's, positive body image (Homan et al, 2018). Although these studies suggest a direct link between attachment anxiety and positive body image, indirect pathways are also possible.…”
Section: Introductionmentioning
confidence: 99%